The Everyday Lives of Gay Men Autoethnographies of the Ordinary - Rodríguez-Dorans, Edgar; Holmes, Jason (Transforming LGBTQ Lives, 2022)
The Everyday Lives of Gay Men draws on the expertise of 12 contributors from different countries and fields, writing from an autoethnographic first-person approach. Putting the power of personal stories at the centre of the construction of sophisticated narratives of gay men's lives, the accounts draw attention to the limits of traditional perspectives to gay men's studies that look at gayness through a sexualised lens and explore how gay men make sense of their identity in their everyday lives. Together they present a complex, nuanced understanding of gayness and challenge the conception of 'being gay' as a sexual orientation because it describes in sexual terms an identity that is not only, not always, and not predominantly sexual. The authors come from a variety of fields, including counselling studies and sociology, to communication, religion, and education. The innovative approach of The Everyday Lives of Gay Men makes it ideal for students and scholars in gender studies, sexuality studies, sociology, mental health, and research methods. The Open Access version of this book, available at www.taylorfrancis.com/books/e/9780367676834, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.